The best sons of the fatherland : workers in the vanguard of Soviet collectivization - Viola, Lynne (New York : Oxford University Press, 1987)
Bibliiotheek F. Vercammen
Engels
Monografie
Keywords: 1925-1935.; collectivisme; economische politiek; Sovjet-Unie.